Analysis Of The Application Of Halal Lifestyle Among University Students - Aulia Azman, Heru; Thahirah , Khadijah Ath; Putri, Siska Lusia (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The awareness of consuming halal products is an important issue for Muslim consumers today. So that producers are obliged to guarantee the halalness of the products they produce. Product halalness aims to provide protection for Muslim consumers around the world, as well as a strategy to face the challenges of globalization with the implementation of a free market system within the framework of ASEAN-AFTA, NAFTA, the European Economic Community, and the International Trade Organization (World Trade Organization). Even the international trade system has long recognized halal provisions in CODEX which are supported by influential international organizations including WHO, FAO, and WTO. The Royal Islamic Strategic Studies Center (RISSC) report entitled The Muslim 500 2023 edition shows that the Muslim population in Indonesia reaches 237.55 million. This number is the largest in the Association of Southeast Asian Nations (ASEAN) countries, as well as globally. The Muslim population in Indonesia is equivalent to 86.7% of the total population in Indonesia. This makes Indonesia's position very favorable, especially as the world's largest market in terms of consumption of the halal industry, such as fashion products, cosmetics, medicines, and the tourism sector. With the largest Muslim population in the world, Indonesia is certainly an opportunity for world producers to expand their distribution channels to Indonesia. The opportunity for the development of the halal industry has certainly become a big dream for Indonesia, with all its natural wealth and cultural diversity, Indonesia should be able to compete with the industrial quality of halal industry exporting countries in other countries. The trend of halal lifestyle has grown globally. Many countries in different parts of the world are trying to implement the halal system in their daily lives. Most Muslims agree that they should always choose halal products in accordance with Islamic sharia. However, there is a unique fact that the concept of halal lifestyle is not only applied by Muslims who are often synonymous with halal choices. The halal lifestyle has also been followed by non-Muslim consumers who are becoming aware of halal products (Rezai et al., 2012). Although the halal concept has not become the main element among non-Muslim consumer choices, factors such as geographical location, education level, and income are the basis for non-Muslim consumers to consume halal products (Teng et al., 2013). Halal lifestyle or often called halal lifestyle has actually become a common thing for the community, both in Indonesia and in other countries, even though it is not a Muslim country. The development of digital technology makes it easy for people to learn and explore the benefits of a halal lifestyle. Halal lifestyle is a person's lifestyle that can determine behavior in making a decision regarding something that is required, permitted, or prohibited according to Islamic law. So, halal is not only related to food, but also involves discussions related to other aspects of human life. Halal lifestyle is also said to be a person's right and good way of life by following the principles of sharia and the main provisions regarding something halal and haram. The word halal is a word derived from Arabic which has meaning in the interpretation of the Qur'an, namely everything that has been permitted and permitted by sharia. In this case, sharia explains the existence of an order of life and all restrictions are clear in consuming food and drink, and regulates the attitude as a human being in carrying out his personal and social life and muamalah (Bahatma, 2021). Halal lifestyle is now a prerequisite for fulfilling needs. In other words, a halal lifestyle means a person's attitude and lifestyle in daily activities (activities, interests, opinions) in accordance with sharia principles (based on the Qur'an and Hadith) (Yetty & Priyatno, 2021). According to the Islamic Judicial Halal Trust (MJCHT), a halal lifestyle is an action that is carried out honestly, correctly, with integrity, dignity and fairness, in accordance with individual abilities, and does not deviate from Islamic law (Z. Sari et al., 2022). Therefore, with this sharia lifestyle, Muslims will prefer products and use sharia-compliant services that comply with Islamic norms. In addition, the halal lifestyle has elements of health, safety, welfare, and human dignity. In other words, the sharia lifestyle is not intended to provide any prohibitions or restrictions. Rather, it is used to reintroduce the values of Islamic teachings that are Rahmatan Lil'Alamin.